Psychedelics disrupt hierarchical cortical propagations in the default mode network of humans and mice - Adam R. Pines; Xue Zhang; John Kochalka; Sam S. Vesuna; Isaac V. Kauvar; Divya Rajasekharan; T. Rick Reneau; Teddy J. Akiki; Laura M. Hack; Joshua S. Siegel; Leanne M. Williams (Proceedings of the National Academy of Sciences, 2026)
Psychedelic drugs are poised to become mainstream treatments, yet we lack a circuit-level account of how they reshape brain activity. Emerging evidence suggests that multiple psychedelic compounds modulate activity in the brain’s default mode network (DMN), often interpreted as either increased or decreased bottom–up hierarchical processing. Most imaging studies, however, quantify activity as if it were stationary, remaining agnostic to the ascending or descending movements of activity that defines hierarchical processing. Here, we adapt optical flow analyses to track frame-to-frame trajectories of DMN activity across four independent datasets (humans and mice; methylenedioxymethamphetamine, psilocybin, and lysergic acid diethylamide; nine drug-vs.-control contrasts). In functional magnetic resonance and calcium imaging, all psychedelics attenuate signal flow magnitude and bottom–up directionality within the DMN. Propagation attenuation is not attributable to data quality or previously documented effects of psychedelics and is uniquely associated with self-reported outcomes. This replicable and generalizable attenuation of bottom–up cortical propagations provides fundamental clarification of the effects of psychedelics on macroscale hierarchical processing.